Design representation of the multipurpose Fuzzy Logic controller using hardware description language - Zeyad Assi, Obaid; Nasri, Sulaiman; M. N., Hamidon; Mohammed Obaid, Ali (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.